2013
DOI: 10.1136/archdischild-2012-303157
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural, educational and respiratory outcomes of antenatal betamethasone for term caesarean section (ASTECS trial)

Abstract: ObjectivesTo determine whether antenatal betamethasone prior to elective term caesarean section (CS) affects long term behavioural, cognitive or developmental outcome, and whether the risk of asthma or atopic disease is reduced.DesignA questionnaire based follow-up of a multicentre randomised controlled trial (Antenatal Steroids for Term Elective Caesarean Section, BMJ 2005).SettingFour UK study centres from the original trial.Participants862 participants from the four largest recruiting centres, 92% of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 25 publications
0
95
1
6
Order By: Relevance
“…In pregnancies between 34 and 36 weeks’ gestation, prenatal steroids also reduce risk of short-term respiratory morbidity but not mortality, and there is increased risk of neonatal hypoglycaemia [23]. Long-term follow-up data are broadly reassuring, albeit sketchy [24], and given the potential for long-term side-effects, steroids are not currently recommended for women in spontaneous preterm labour after 34 weeks [25]. When given before elective Caesarean section (CS) up to 39 weeks, they reduce risk of admission to NICU, although the number needed to treat is >20 and follow-up data on term babies exposed to antenatal steroids are lacking [26].…”
Section: Prenatal Carementioning
confidence: 99%
“…In pregnancies between 34 and 36 weeks’ gestation, prenatal steroids also reduce risk of short-term respiratory morbidity but not mortality, and there is increased risk of neonatal hypoglycaemia [23]. Long-term follow-up data are broadly reassuring, albeit sketchy [24], and given the potential for long-term side-effects, steroids are not currently recommended for women in spontaneous preterm labour after 34 weeks [25]. When given before elective Caesarean section (CS) up to 39 weeks, they reduce risk of admission to NICU, although the number needed to treat is >20 and follow-up data on term babies exposed to antenatal steroids are lacking [26].…”
Section: Prenatal Carementioning
confidence: 99%
“…28 93% of the original cohort were able to be contacted, but only 51% completed the questionnaires that served as the basis for the assessment. 28 While there were no differences in behavior and health for the subjects at 8-15 years of age, a higher incidence of being in the lowest quarter of academic ability was noted in the betamethasone group (17.7% vs 8.5%). 28 Several studies have examined the metabolic and hormonal effects of ANCS administered in the late preterm period.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 72%
“…Glucocorticoid-exposed children were twice as likely to be identified as being in the lowest achievement group at school compared with the control group (33 of 186 [17.7%] vs 14 of 164 [8.5%], relative risk, 2.1; 95% CI, 1.1-3.7; P = .01). 3 The authors commented that this result "appeared a discordant finding." 3(pF199) No objective testing of academic ability was performed within the trial.…”
Section: Results Of Long-term Follow-up Of the Astecs Trialmentioning
confidence: 90%
“…The long-term follow-up of the ASTECS trial by Stutchfield et al 3 has recently been published. The authors concluded that "antenatal betamethasone did not result in any adverse outcomes… it should be considered for elective cesarean section at 37-38 weeks of gestation."…”
mentioning
confidence: 99%